Peran UMKM Sebagai Wadah Inkubasi Kewirausahaan Bagi Mahasiswa Dalam Program Wirausaha Merdeka - Mochammad Hendy Dwi Permana; Awin Mulyati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
One pointer of a country's advance can be seen from its financial perspective. MSMEs, as the spine of national financial improvement, require back from the government. Through the Free Enterprise (WMK) program, the government is collaborating with colleges in Indonesia to create a youthful era with an entrepreneurial soul. In this program, understudies are straightforwardly included through the entrepreneurial hatching arrange known as the submersion organize. At this arrange, students' entrepreneurial abilities are sharpened with MSMEs that are accomplices in this program. This think about employments a expressive strategy with a subjective approach. The information displayed were gotten through writing considers by analyzing different sources from past investigate, and are the comes about of work hones carried out with Bulgrill MSMEs.